The political economy of wilkiality: a South African inquiry into knowledge and power on wikipedia - Ovesen, Håvard (Centre for Film and Media Studies, 2014)
This dissertation explores how knowledge construction on the English-language Wikipedia produces hegemonic representations of South Africa. Using Wikipedia's entries on Cape Town and various places in the Free State province as case studies, this dissertation demonstrates through critical discourse analysis that there is a systematic marginalisation, underrepresentation, and decontextualisation of 'black' working class communities and spaces, which echoes their historical marginalisation. This representation is contextualised through a historical narrative of Cape Town and the Free State, and explored against a theoretical background which, borrowing from Foucault, Castells, and others, sees the social construction of knowledge as an expression of power, and the networked society as an arena for the dynamics of hegemony. While Wikipedia is often hailed as a game-changer, the knowledge it produces tends to replicate and, thanks to its ever-increasing reach, further entrench hegemonic explanations of society. This might seem counter-intuitive given its credentials as a democratiser of knowledge, but can be explained with Wikipedia's architecture, which ultimately rests upon a regime of truth established during the Enlightenment. The online encyclopedia relies on well-established institutions and discourses of knowledge as sources of its content, and these, coupled with its particular preferences for some sources and topics over others, give it a particular slant in favour of the hegemonic status quo. The discourse it produces is given further gravitas and is naturalised through an insistence upon the knowledge it presents as 'neutral'. Studies have shown that Wikipedia's values are defined by its established community of editors and that, even as Wikipedia's reach is extending, it is increasingly difficult for new users to impact upon the online encyclopedia. Arguably it is rather the encyclopedia which impacts upon them by circulating seemingly uncontested representations of their communities, or, alternatively, simply ignoring the communities altogether. In a process I have, borrowing from American political satirist Stephen Colbert, termed wikiality, hegemonic representations have a tendency of becoming true when we act upon them as such. Thus, when certain communities are presented as marginal or unimportant, it becomes even more difficult for them to break out of this mould. Meaningful participation on Wikipedia can only be achieved if the user not only has access to relevant technological capital, but also the cultural capital required to make contributions which appeal to the established core of editors. In South Africa, as a result of its political economy, large parts of the population are politically, economically, and socially marginalised. This also means that they lack the cultural capital necessary to make meaningful contributions to Wikipedia. This tends to render them the subjects of Wikipedia entries, rather than their authors, which contributes to their further marginalisation. The key to understanding the relationship between knowledge and power on Wikipedia lies in the ability of some users to capture and define reality through representation and thereby effectuating it. Reducing this imbalance to a simple question of access downplays the social, economic, and political factors which created it in the first place, and accommodates discursive practices which downplay difference and perpetuate hegemony.